Physicochemical and sensory evaluations of moisturising lip balm using natural pigment from Beta vulgaris. Issue 1 (1st January 2020) - Azmin, Siti Nuurul Huda Mohammad; Jaine, Nurshafieera Idayu Mat; Nor, Mohd Shukri Mat
Abstract: Nowadays, people are demanding on the naturally derived cosmetic products, including lip balms. However, there is a lack of studies for the physicochemical properties of the formulated lip balms. Besides, there are little publications found on the use of beetroot as an active ingredient and colourant in lip balm formulation. Thus, this study aims to formulate lip balm using beetroot; and test the physicochemical properties of formulated lip balms to get three best formulations. The stability of these best lip balms was conducted for 4 weeks in room temperature and chiller conditions. Finally, a sensory evaluation was conducted to identify consumer acceptance towards the best lip balms. Lip balms placed in room temperature were all stable while few changes occurred for the lip balms placed in a chiller. All panellist preferred the same lip balm in the sensory test. The result of this study can be extended to assess the potential of beetroot in the formulation of other cosmetic products.